2018
DOI: 10.1016/j.jtcvs.2017.11.081
|View full text |Cite
|
Sign up to set email alerts
|

Correction of postpneumonectomy syndrome with tridimensional carbon fiber–printed implant

Abstract: Video clip is available online. An 18-year-old woman presented with a more than 6-month history of recurrent dyspnea, wheezing, recurring right bronchopneumonia, and tachycardia after left pneumonectomy 2 years previously for an adenoid cystic carcinoma of the left main-stem bronchus. Thoracic computed tomography revealed a shift of mediastinal contents and parts of the right lung into the left hemithorax (Figure 1, A and B). The heart abutted the left lateral rib cage, and the vena From the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Saline-filled tissue expanders were used either alone or in combination with fixed-volume prostheses in 28 patients (32.2%), allowing percutaneous volume adjustment. Wang et al described the use of a 3D carbon fibre-printed implant with good results [ 5 ]. Sizing of prostheses was reported in 18 studies with perioperative CVP monitoring (n = 7) and bronchoscopic assessment of airway compression (n = 8) being the most common approaches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saline-filled tissue expanders were used either alone or in combination with fixed-volume prostheses in 28 patients (32.2%), allowing percutaneous volume adjustment. Wang et al described the use of a 3D carbon fibre-printed implant with good results [ 5 ]. Sizing of prostheses was reported in 18 studies with perioperative CVP monitoring (n = 7) and bronchoscopic assessment of airway compression (n = 8) being the most common approaches.…”
Section: Resultsmentioning
confidence: 99%
“…McRae et al described the successful use of a custom-made tissue expander with a wall three times as thick as normal implants [ 10 ]. Custom made, patient-specific prostheses, as well as 3D carbon-fibre printed prostheses, have also been described with good results [ 5 , 26 ]. In cases where patients develop severe airway malacia following mediastinal repositioning, airway stenting may relieve symptoms, as described by Kelly et al [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported several articles on the treatment of PPS, including tissue expander implantation [ 3 6 ], gas injection [ 7 , 8 ] and stenting [ 9 ]. Unfortunately, tissue expanders for thoracic cavity stabilization are not approved for use in Japan due to insurance regulations, which limits their availability for emergency surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patch floating would have occurred if we had performed trachea repair with an autologous pericardial patch alone because of the large-sized defect, and tracheal stenosis and obstruction can easily occur in the late postoperative period. Therefore, combining the results of Aria's study with our own experience with 3D carbon fiber reconstruction implants (6)(7)(8), we designed a customized 3D carbon fiber stent outside the pericardial patch. The floating of the patch and tracheal stenosis were avoided by applying stent traction.…”
Section: Discussionmentioning
confidence: 99%